Mapping millet value chain in Fatick, Senegal - Fall, Modou; Sall, Moussa; Diakhaté, Pape Bilal; Cesaro, Jean-Daniel; Diao Camara, Astou (2023)
With a view to enabling the millet value chain to play a key role in the creation of wealth, jobs and conditions of socio-economic stability in the terroirs, this study aims to analyze the millet value chain in order to identify the obstacles and action levers for the co-design of a sustainable value chain that is sensitive to the principle of agroecology in the Fatick region in Senegal.